Adsorption of BiOBr microspheres to rhodamine B and its influence on photocatalytic reaction - Liang, Congjie; Ma, Jian; Cao, Yixi; Zhang, Taisong; Yang, Chanyu; Wu, Yingfeng; Li, Huaming; Xu, Hui; Hua, Yingjie; Wang, Chongtai (Chemosphere (Oxford), 2022)
Adsorption and its influence are often neglected during photocatalytic degradation of organic pollutants. To call attention to these issues, a novel bismuth oxybromide (BiOBr) microsphere with hierarchical flower-like structure was fabricated through a facile hydrothermal process using polyvinyl pyrrolidone (PVP) as additive in this work, and then the adsorption of the BiOBr microspheres to RhB and its influence on the photocatalytic degradation of RhB were investigated in detail. Experimental results show that the BiOBr microspheres have a very strong adsorption capacity to RhB. The adsorption behavior follows the Langmuir model and the quasi second order kinetic equation. Tests of the photocatalytic degradation of RhB under visible irradiation verify that the adsorption of the BiOBr microspheres to RhB greatly boosts the degradation of RhB due to the “enriching effect”, and a complete degradation of 20 mg L−1 RhB only requires 37 min. [Display omitted] •The adsorption behavior of photocatalyst was detailedly studied using the synthesized BiOBr microspheres.•The adsorption model and parameters were determined through experiments.•The remarkably improved adsorption capacity of BiOBr microspheres was explained through experiments and DFT calculation.•The strong adsorption of the BiOBr microspheres to RhB was proved to facilitate its photodegradation.•This work provides new insights into adsorption phenomenon during photocatalytic degradation of organic dyes.